Dinamika Pengakuan Penghayat Kepercayaan di Indonesia - Kristina Viri; Zarida Febriany (Indonesian Center for Religion and Society Studies (InTReSt), 2020)
Indonesia has various local religions that live a hundred years, even before independence. These religions are known as “Penghayat Kepercayaan”. In history, the adherents of these beliefs experienced hardship dynamics to gain recognition from the State. The methodology that has been used for this research is a normative juridical or documentary study with qualitative analysis. The result and discussions of this research concluded that Article 28E of the 1945’s Constitution guaranteed everyone to have the right of freedom to believe. However, the reality is the opposite as the State is discriminating between the officials and the unofficial religions. Because of the long struggles of the stakeholders, the community of Penghayat Kepercayaan has pleaded to the Constitutional Court (MK) for a judicial review, and it was accepted. MK has stated that discrimination between the official and the unofficial religions is a contradiction to the 1945’s Constitution. Based on the decision of MK, the State recognizes the community of Penghayat Kepercayaan, especially for all the matters related to their rights for civil administration (where now, there is a “belief” column for them, in the Family Card and electronic ID), and their rights to embrace and worship.